2015
DOI: 10.1002/pbc.25731
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Low‐Grade Gliomas in Children: 20 Years' Experience at St. Jude Children's Research Hospital

Abstract: Background Patients with low-grade gliomas (LGG), which are the most common childhood brain tumors, have excellent long-term survival. Dissemination of LGG is rare. Robust data on the incidence, presentation, patterns of dissemination, disease behavior, outcome, and best-management approaches do not exist. We describe 20 years of follow-up of children with metastatic LGG. Procedure Data collected during the period 1990–2010 were retrospectively reviewed for the following inclusion criteria: diagnosis of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 65 publications
4
35
1
Order By: Relevance
“…An inability to achieve GTR of the tumor upfront, diencephalic syndrome, and possibly an HT/OP tumor location were associated with inferior PFS in our cohort; this is similar to observations of pediatric LGGs over the entire age spectrum . In agreement with previous studies, the proportion of infants with metastasis in our cohort was higher than that in pediatric LGG, but unlike in older patients, metastasis in infant LGG did not affect survival …”
Section: Discussionsupporting
confidence: 91%
“…An inability to achieve GTR of the tumor upfront, diencephalic syndrome, and possibly an HT/OP tumor location were associated with inferior PFS in our cohort; this is similar to observations of pediatric LGGs over the entire age spectrum . In agreement with previous studies, the proportion of infants with metastasis in our cohort was higher than that in pediatric LGG, but unlike in older patients, metastasis in infant LGG did not affect survival …”
Section: Discussionsupporting
confidence: 91%
“…Metastatic imaging work‐ups were available for 59 (68%) patients at diagnosis, seven of who had evidence of dissemination. This contrasts with a finding of 19 patients with metastatic disease at diagnosis in a larger cohort of 599 patients with LGG, alive or dead, reported from our institution by Chamdine et al . All patients had at least one imaging examination (either computed tomography or MRI) to investigate for dissemination.…”
Section: Resultscontrasting
confidence: 84%
“…The median age at diagnosis in our cohort was 4.0 years, which is similar to what has been reported in previous studies . Our study included more females (59%) whereas other studies have reported a male predominance in LGGs .…”
Section: Discussionsupporting
confidence: 87%
“…The median age at diagnosis in our cohort was 4.0 years, which is similar to what has been reported in previous studies. 14 Our study included more females (59%) whereas other studies have reported a male predominance in LGGs. 7 This might be explained by the fact that patients with optic pathway glioma are more often female than male and 86% of our cohort had optic pathway glioma.…”
Section: Discussionmentioning
confidence: 77%